The value of practice-based collaborations across the third space: reflections on supporting multimodal assignments - Lauren Cross; Sara Sharun; Luciano da Rosa dos Santos (Journal of Learning Development in Higher Education)
Multimodal assignments are becoming a prevalent strategy to enable assessment of student learning (Reid et al., 2016). However, due to their inherent complexity, supporting faculty members and students in adopting and implementing these types of assignments can be challenging (Wysocki et al., 2019). To overcome this, a group of ‘third space’ (Whitchurch, 2013) academic professionals came together to design and implement a support system that considered these assignments holistically. In this opinion piece, we reflect on the creation of a lifecycle approach to supporting multimodal assignments that built awareness and deepened understanding among faculty of our roles in teaching and learning. We also share how our informal, transdisciplinary collaboration can serve as a precursor for similar projects that support students and faculty.